Pseudomonas moraviensis subsp. stanleyae, a bacterial endophyte of hyperaccumulator Stanleya pinnata, is capable of efficient selenite reduction to elemental selenium under aerobic conditions - Staicu, L C; Ackerson, C J; Cornelis, P; Ye, L; Berendsen, R L; Hunter, W J; Noblitt, S D; Henry, C S; Cappa, J J; Montenieri, R L; Wong, A O; Musilova, L; et al. (Journal of applied microbiology, 2015)
AIMS: To identify bacteria with high selenium tolerance and reduction capacity for bioremediation of wastewater and nanoselenium particle production. METHODS AND RESULTS: A bacterial endophyte was isolated from the selenium hyperaccumulator Stanleya pinnata (Brassicaceae) growing on seleniferous soils in Colorado, USA. Based on fatty acid methyl ester analysis and multi-locus sequence analysis (MLSA) using 16S rRNA, gyrB, rpoB and rpoD genes, the isolate was identified as a subspecies of Pseudomonas moraviensis (97.3% nucleotide identity) and named P. moraviensis stanleyae. The isolate exhibited extreme tolerance to SeO3(2-) (up to 120 mmol l(-1)) and SeO4(2-) (>150 mmol l(-1)). Selenium oxyanion removal from growth medium was measured by microchip capillary electrophoresis (detection limit 95 nmol l(-1) for SeO3(2-) and 13 nmol l(-1) for SeO4(2-)). Within 48 h, P. moraviensis stanleyae aerobically reduced SeO3(2-) to red Se(0) from 10 mmol l(-1) to below the detection limit (removal rate 0.27 mmol h(-1) at 30 °C); anaerobic SeO3(2-) removal was slower. No SeO4(2-) removal was observed. Pseudomonas moraviensis stanleyae stimulated the growth of crop species Brassica juncea by 70% with no significant effect on Se accumulation. CONCLUSIONS: Pseudomonas moraviensis stanleyae can tolerate extreme levels of selenate and selenite and can deplete high levels of selenite under aerobic and anaerobic conditions. SIGNIFICANCE AND IMPACT OF THE STUDY: Pseudomonas moraviensis subsp. stanleyae may be useful for stimulating plant growth and for the treatment of Se-laden wastewater.
Keywords: Aerobiosis; Biodegradation, Environmental; Endophytes; endofyty; aerobióza; selen; Brassicaceae; biodegradace; Selenious Acid; Pseudomonas; kyselina seleničitá; Selenium